2020
DOI: 10.1038/s41598-020-58683-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison of Yarrowia lipolytica and Pichia pastoris for production of Candida antarctica lipase B

Abstract: The large-scale production of recombinant proteins (rProt) is becoming increasingly economically important. Among the different hosts used for rProt production, yeasts are gaining popularity. The socalled non-conventional yeasts, such as the methylotrophic Pichia pastoris and the dimorphic Yarrowia lipolytica, are popular choices due to their favorable characteristics and well-established expression systems. Nevertheless, a direct comparison of the two systems for rProt production and secretion was lacking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…It has been previously suggested that although P. pastoris is naturally capable of producing large amounts of proteins in response to methanol, it is not naturally prone to high-level secretion of proteins. In contrast, Y. lipolytica naturally secretes high levels of various native enzymes and hence its secretory pathway is naturally less prone to induce endoplasmic reticulum (ER) associated degradation (Theron, Vandermies, Telek, Steels, & Fickers, 2020). Although Y. lipolytica's native potential in this regard is highly competitive (alkaline extracellular protease can be secreted up to 2 g L −1 ; Le Dall, Nicaud, & Gaillardin, 1994;Ogrydziak, 2013), it is interesting to systematically study different parameters that enable further enhancement of this trait by both bioprocessing (Vandermies & Fickers, 2019) and genetic engineering approaches (Celi nska, Borkowska, Białas, Korpys, & Nicaud, 2018).…”
mentioning
confidence: 99%
“…It has been previously suggested that although P. pastoris is naturally capable of producing large amounts of proteins in response to methanol, it is not naturally prone to high-level secretion of proteins. In contrast, Y. lipolytica naturally secretes high levels of various native enzymes and hence its secretory pathway is naturally less prone to induce endoplasmic reticulum (ER) associated degradation (Theron, Vandermies, Telek, Steels, & Fickers, 2020). Although Y. lipolytica's native potential in this regard is highly competitive (alkaline extracellular protease can be secreted up to 2 g L −1 ; Le Dall, Nicaud, & Gaillardin, 1994;Ogrydziak, 2013), it is interesting to systematically study different parameters that enable further enhancement of this trait by both bioprocessing (Vandermies & Fickers, 2019) and genetic engineering approaches (Celi nska, Borkowska, Białas, Korpys, & Nicaud, 2018).…”
mentioning
confidence: 99%
“…Three strains exhibiting no significant difference in the activity were selected for further studies. As demonstrated previously, such strategy enables selection of strains with only a single expression cassette integrated in a neutral site in the genome, ensuring negligible inter-clone variation [9,41].…”
Section: Design and Construction Of Y Lipolytica Recombinant Strainsmentioning
confidence: 94%
“…Taking advantage of the progress within this field, it is now feasible to generate a number of variants of complex genetic constructions to carefully study and optimize their design, so that expression of target genes is adjusted to the requirements of a specific bioprocess. Due to unique native metabolic properties, like intrinsically high production of lipids [6], polyols [7], organic acids [8], and recently evidenced superior capacity for heterologous proteins production over a typical workhorse in this regard -Komagataella phaffi (P. pastoris) [9], Y. lipolytica stains are frequently subjected to genetic modifications broadening its scope of utilized substrates, with the aim to improve economic feasibility of production processes [10]. For example, Y. lipolytica strains has been endowed with artificial ability to grow on sucrose [11], inulin [12], galactose [13], starch [14] or even cellulose [15,16].…”
Section: Decomposition Of Complex Substrates Requires Orchestrated Acmentioning
confidence: 99%
See 2 more Smart Citations